PEMANFAATAN LIMBAH CANGKANG KELAPA SAWIT SEBAGAI PENGANTI FILLER DAN PENAMBAHAN ADITIVE ANTI STRIPING PADA CAMPURAN ASPAL BETON - LAPIS ANTARA (AC-BC) - Setiawan, Jimmi; Firdaus, Firdaus (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Flexible pavement in Indonesia in the form of Asphalt Concrete roads or better known as asphalt concrete (Laston), the high and low level of highway users determines the durability of the road, the increase in highway users, the increase in traffic load on asphalt which will reduce the durability or durability of asphalt will decrease, causing damage to the asphalt surface, , writing and this research uses waste from palm shell burning ash as a substitute for ash filler resulting from oil palm shell burning will be used by 1%, 1,5%, 2%, and 2,5% of the total weight of the aggregate and using additional materials in the form of anti-peeling materials (Anti Striping) quantity for the use of anti-striping additives that are appropriate in the 2018 revision 2 specification in vulnerable as much as 0,20% to 0,40% of the weight of asphalt used in one production times or as much as 0,20%, up to 0,40% of the weight of asphalt used in the manufacture of one marshal test piece, In this study, only 0,20%, 0,30%, 0,40%, and 0,50% anti-striping additives will be used against the weight of 60/70 penetration asphalt One way to replace the use of filler on concrete asphalt or utilize palm shell waste by using ash from the combustion of palm shell waste contains palm shell ash in the form of silicon oxide (SiO2) which has similar reactive properties to cement and pozzolanic activity has a reaction to become a Hard and stiff material to meet the durability as a substitute for filler.Keywords : Concrete Asphalt, Palm Shell Ash, Anti-Stripi